Disciplining land through data: The role of agricultural technologies in farmland assetisation. Issue 2 (23rd March 2022) - Duncan, Emily; Rotz, Sarah; Magnan, André; Bronson, Kelly
Abstract: Digital agricultural technologies are promoted for increasing productivity, environmental sustainability and transparency in farming. Critical perspectives on digital agriculture are necessary to frame opportunities and challenges for agricultural communities. However, the ways in which digital agricultural technologies are contributing to land financialisation—bringing land into the global market exchange—remains unexplored. Historically, farmland has been difficult to incorporate into global markets; the complex environments of family ownership have made farms difficult to condition, discipline and control, which has deterred investors. While the outright ownership of farmland has been unappealing to investors until recently, land ownership is becoming increasingly attractive due to technological change and shifts in land management. We use a responsible research and innovation framework to examine the movements in land via digitalisation asking: Who benefits and who loses due to these processes? And what are the consequences? We bring together the agro‐food financialisation scholarship, critical data studies and responsible innovation literature to bear on an analysis of farmer interviews and content from institutional investors. Ultimately, we argue that digital technologies, through their connection with land assetisation, are fostering growing inequities with respect to land access and farmer autonomy, and thus do not presently constitute responsible innovation.